2020
DOI: 10.3390/ijerph17072286
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dog Presence on Stress Levels in Students under Psychological Strain: A Pilot Study

Abstract: As university students face many stressful situations, especially during the examination period, this study focused on the use of animal-assisted activities (AAAs) with a dog as a means of relieving students’ stress before a final exam. The aim was to determine whether a 10-min interaction with a dog affected subjectively evaluated stress and mood, objective blood pressure, and heart rate. Ninety-three female students (mean age = 22.5 years; standard deviation = 3.8 years) were divided into three groups accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 48 publications
0
6
0
1
Order By: Relevance
“…Nevertheless, an effect on students’ physical well-being did not occur in this study. The influence dogs have on students’ physical well-being cannot be unambiguously answered, as some studies have linked DAI in higher education to improvements in health factors such as lower blood pressure and cortisol levels [ 32 , 42 , 43 , 81 ], while other studies have failed to confirm such effects [ 29 , 36 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, an effect on students’ physical well-being did not occur in this study. The influence dogs have on students’ physical well-being cannot be unambiguously answered, as some studies have linked DAI in higher education to improvements in health factors such as lower blood pressure and cortisol levels [ 32 , 42 , 43 , 81 ], while other studies have failed to confirm such effects [ 29 , 36 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although providing this kind of intervention to college and university students is a fairly new undertaking [ 26 ], there is promising evidence that AAIs can, amongst others, result in higher ratings of momentary positive emotions, a reduction in stress-related negative emotions [ 27 , 28 ], psychological and physical markers of stress [ 29 , 30 , 31 , 32 ], anxiety [ 33 , 34 , 35 , 36 ], and homesickness while increasing their satisfaction with life, connectedness to campus [ 37 , 38 ], behavioral aspects of academic success [ 39 ], well-being and improving their social skills as well as their mood [ 29 , 33 , 40 ]. Furthermore, Daltry and Mehr [ 41 ] found that having animals on campus may promote the services offered by student counseling centers on campus, as a lot of students were unaware of them before implementing the AAI.…”
Section: Introductionmentioning
confidence: 99%
“…In this category, we included studies with control conditions where subjects were asked to sit and relax for a certain amount of time (Fiocco and Hunse, 2017 ; Machová et al, 2020a , b ). We found that nine studies controlled for relaxation as a non-specific factor.…”
Section: Resultsmentioning
confidence: 99%
“…While human–animal interaction was mentioned by several authors as a specific factor, human–animal interaction comprises a multitude of components. For example, several studies hypothesized that human–animal interaction can reduce stress (Fiocco and Hunse, 2017 ; Pan et al, 2019 ; Machová et al, 2020b ), but they did not specify how human–animal interaction leads to this possible stress-reducing effect. These rather vague factor hypotheses about human–animal interaction and AAIs reflect the current problem in the AAI research where the question of how AAIs work is still neglected (López-Cepero, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…King [149] wrong study design Kobayashi et al [150] wrong outcomes Kronholz et al [151] wrong study design Kuzara et al [152] wrong outcomes Lacoff et al [153] wrong study design Lauriente et al [154] wrong study design Lephart et al [155] wrong study design Linden [156] criteria for inter-library loan not met Litwiller et al [157] wrong study design Machova et al [158] wrong study design Malakoff [159] wrong population…”
Section: References Of Excluded Studies From Full Manuscript Search Reason Excludedmentioning
confidence: 99%